Determinants of Foreign Direct Investment Performance – a Critical Literature Review - Trapczynski, Piotr (Oeconomia Copernicana, 2013)
Foreign direct investment (FDI), its motives, modes and location choice constitute key subjects in theory and research in international business, due to their long-term consequences for firm competitiveness. The determinants of results achieved in foreign markets can therefore be described as a fundamental research area, which specifically includes studies on FDI performance. In spite of its long tradition and methodical advancement, extant research show numerous inconsistencies and ambiguous findings. In both international and Polish literature, no complex summary of extant knowledge on FDI performance determinants can be found, which would allow for the consolidation and evaluation of earlier findings. The aim of this paper is to present the findings of a structured review of 95 studies on performance of foreign subsidiaries. Within extant studies, four main research streams were identified, focusing on FDI mode choice, resource determinants on a firm and subsidiary level, host-country characteristics and corporate strategy. Previous research has not adequately considered the role of expansion motives for evaluating FDI performance. Future studies should also to a greater extent account for a differentiated role of firm resources, particularly various types of international experience, as applied in host countries at different levels of economic and institutional development. Moreover, a more holistic FDI performance analysis requires a simultaneous consideration of financial and non-financial dimensions of a foreign subsidiary's competitive position. Based on the outcomes of the present review, areas for further studies have been proposed, especially as regards the context of outward FDI, increasingly undertaken by Polish companies, and its specific character.